Model Pembelajaran Bahasa Inggris Anak Tunanetra Berbasis Permainan Scrabbel Braille - Irdamurni, Irdamurni; Sumekar, Ganda; Nopitasari, Marlina (Jurusan Pendidikan Luar Biasa Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2017)
Blind children have very minimal English vocabulary, so a learning model is needed to improve the English vocabulary of the blind. The type of research is research development (R & D), which refers to the theory of Borg and Gall (1983). The subjects of the study were blind class VIII students in SLB A Payakumbuh. The research produced an English learning model based on Scrabbel Braille Game, and an effective Braille Scrabble game to improve the English vocabulary of the blind.